2016
DOI: 10.1037/bul0000034
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing reconsolidation to weaken fear and appetitive memories: A meta-analysis of post-retrieval extinction effects.

Abstract: A new understanding of the mechanisms of memory retrieval and reconsolidation holds the potential for improving exposure-based treatments. Basic research indicates that following fear extinction, safety and fear memories may compete, raising the possibility of return of fear. One possible solution is to modify original fear memories through reconsolidation interference, reducing the likelihood of return of fear. Post-retrieval extinction is a behavioral method of reconsolidation interference that has been expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
176
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(204 citation statements)
references
References 108 publications
(208 reference statements)
9
176
1
3
Order By: Relevance
“…A recent meta-analysis of these and similar studies found that the effects of postretrieval extinction on relapse in animals are typically small and often nonsignificant (Kredlow et al, 2016), which is in line with the current data. That said, in cases where postretrieval extinction was successful, Kredlow and colleagues (2016) found housing conditions and the timing of retention testing to be important factors in the effect. Specifically, the authors found that housing conditions were a significant moderator of postretrieval extinction, such that group housing appeared to reduce the efficacy of postretrieval extinction.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A recent meta-analysis of these and similar studies found that the effects of postretrieval extinction on relapse in animals are typically small and often nonsignificant (Kredlow et al, 2016), which is in line with the current data. That said, in cases where postretrieval extinction was successful, Kredlow and colleagues (2016) found housing conditions and the timing of retention testing to be important factors in the effect. Specifically, the authors found that housing conditions were a significant moderator of postretrieval extinction, such that group housing appeared to reduce the efficacy of postretrieval extinction.…”
Section: Discussionsupporting
confidence: 89%
“…After conditioning, encountering fear conditioning-related stimuli (the CS, US, and/or conditioned context) can trigger the previously consolidated conditioned memory to enter a labile state that requires reconsolidation (Auber et al, 2013; Clem & Schiller, 2016; Kredlow et al, 2016; Schiller & Phelps, 2011). Behavioral, pharmacological, or neural manipulations during this postretrieval period allows for modification of the fear memory, including weakening or potentially erasing the memory (Auber et al, 2013; Giustino et al, 2016; Kindt et al, 2009; Kindt & van Emmerik, 2016; Lattal & Wood, 2013; Meir Drexler & Wolf, 2016b; Monfils et al, 2009; Nader, 2003, 2015; Nader et al, 2000; Quirk et al, 2010; Schiller et al, 2010; Schwabe et al, 2014; Soeter & Kindt, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extinction paradigms leading to persistent threat memory attenuation therefore present an interesting test case for biochemical signatures of new learning and unlearning, since they can presumably engage either extinction or reconsolidation, but not both. For example, in retrieval-extinction the introduction of an isolated CS trial shortly before extinction prevents the subsequent reemergence of threat memory during spontaneous recovery, renewal and reinstatement tests in both rodents and humans [21, 50, 7180]; although for unknown reasons some studies have failed to replicate these effects (for in-depth reviews see [16, 81, 82]). Reports have favored the interpretation that the initial CS trial destabilizes threat memory and initiates a time-limited lability window during which extinction training can either interfere with memory restabilization or supply new safety-related information that can be integrated into the memory during its reconsolidation.…”
Section: Discrimination On the Basis Of Biochemical Mechanismsmentioning
confidence: 99%
“…Seeking to capitalise on this, a number of studies have examined whether performing extinction trials within the putative 'reconsolidation window' might be more e ective at eliminating fear responses than standard extinction protocols (for review see Auber, Tedesco, Jones, Monfils, & Chiamulera, 2013;Kredlow, Unger, & Otto, 2015). The logic here is that reactivation of a memory trace opens a time-dependent window during which that trace can be modified.…”
Section: Extinctionmentioning
confidence: 99%